Analisis Program Pembangunan Infrastruktur Bendungan terhadap Tingkat Kemandirian Petani di Kecamatan Buke Kabupaten Konawe Selatan - Hulul Abdianto; Muhammad Aswar Limi; Yusran Yusran (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2022)
This research aims to compare farmers' levels of independence before and after receiving government support in Buke District, South Konawe Regency. The second goal was to see whether there was a change in farmers' levels of independence before and after getting government support in Buke District, South Konawe Regency. From June 2021 to February 2022, this study was conducted. The participants in this research were all members of farmer organizations. Using the Slovin algorithm, 49 respondents were selected from each farmer group member for this research. The data was analyzed using quantitative descriptive statistical analysis and t-test analysis. The findings revealed that farmers' degree of independence before obtaining program help from the Directorate General of Water Resources (Development of Damin infrastructure) was poor. The average score received from each indicator fell into the low group. After receiving program help from the Directorate General of Water Resource (Development of Damin infrastructure), farmers' independence is high. Data analysis using a t-test to determine the impact of government assistance on farmer independence reveals a significant probability value, indicating that there is an essential or genuine difference between before and after the assistance program, implying that the Directorate General of Water Resource (Development of Damin infrastructure) program has a positive and significant impact on increasing the independence of lowland rice farmers in Buke District.